Analyse spatiale des violences faites aux femmes au sein du couple dans la ville de Toulouse - Ryan Toutin; Norbert Telmon; Frederic Savall (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Intimate partner violence against women is internationally recognized as a public health and social policy issue of epidemic proportions and a violation of women’s rights. In particular, the occurrence of such violence appears to be correlated with the clustering of socio-economically disadvantaged conditions within the local environment. The aim of our study was to map the distribution of intimate partner violence against women in the city of Toulouse, in order to highlight the presence of spatial interactions. The postal addresses of 840 women who consulted the forensic medicine unit at the Rangueil Hospital in Toulouse were geocoded. The spatial distribution of these addresses was then analysed using spatial smoothing functions, spatial correlation tests and spatial risk estimation models. These revealed a markedly heterogeneous pattern formed by significant spatial groupings, of which some present an estimated relatively high risk of intimate partner violence against women. Because forensic medicine units play a central role in the care of these women, using the large quantity of available data together with innovative methods of spatial epidemiology would help to better understand the mechanisms at play, in order to facilitate the implementation of social, medical and environmental policies aiming to combat violence of this kind.